Identification of novel germline and somatic mutations associated with hepatocellular carcinoma by next-generation sequencing - Laaribi, Ahmed Baligh; Babay, Wafa; Lekired, Abdelmalek; Bouchabou, Bochra; Mehri, Asma; Bacha, Dhouha; Sassi, Riadh; Ben Slama, Sana; Bayar, Rached; Omrani, Sahir; Boujelbene, Nadia; Ennaifer, Rim; et al. (Frontiers in Pharmacology, 2026)
BackgroundHepatocellular carcinoma (HCC) is the third leading cause of cancer-associated deaths worldwide with an estimated of 900,000 new cases annually. HCC typically arises in patients with chronic liver disease, including hepatitis, cirrhosis, and non-alcoholic fatty liver diseases. Identifying of the main driver genetic alterations in oncogenic genes is essential for understanding HCC pathogenesis and defining prognostic biomarkers in high-risk patients. This study aimed to identify both germline and somatic mutations associated with HCC in a Tunisian patient’s cohort.MethodsForty HCC patients with different etiologies were included in this study. Peripheral blood samples were collected from 24 patients with advanced-stage HCC. Paired tumor and adjacent non-tumoral liver tissue samples were obtained from 16 early-stage HCC patients undergoing hepatic resection, including 10 fresh-frozen samples and 6 FFPE samples. DNA was extracted using the MagCore® Plus II system. Targeted next-generation sequencing was performed using the Illumina AmpliSeq™ Cancer Hotspot Panel v2.ResultsA total of 35 germline mutations were identified across 25 genes. Recurrently altered genes included FGFR3 (100%), PDGFRA (100%), RET (98%), APC (92%), TP53 (88%), and EGFR (75%). In addition, 14 somatic mutations were detected in 13 genes, with frequent alterations observed in APC (100%), ALK (94%), HNF1A (56%), CDKN2A (50%), and HRAS (50%).ConclusionThis study offers the first comprehensive overview of novel germline and somatic mutations in Tunisian HCC patients, representing a North African cohort, and highlights key molecular drivers of hepatocarcinogenesis. These findings support the integration of genetic profiling into clinical practice to enhance early diagnosis and guide personalized therapies.